2014
DOI: 10.1530/joe-14-0348
|View full text |Cite
|
Sign up to set email alerts
|

Distinct pathways of cholesterol biosynthesis impact on insulin secretion

Abstract: Results from previous investigations have indicated that glucose-stimulated insulin secretion (GSIS) is affected by changes in cholesterol and its intermediates, but the precise link between secretion and cholesterol has not been thoroughly investigated. In this study, we show the contribution of both protein isoprenylation and cholesterol-dependent plasma membrane structural integrity to insulin secretion in INS-1E cells and mouse islets. Acute (2 h) inhibition of hydroxyl-methylglutaryl-CoA reductase by simv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…A decrease in insulin secretion was observed under long-term inhibition of CH synthesis in insulin-secreting cells [23]. The associated impairment of GSIS is probably due to an effect of reduction in the protein isoprenylation and more importantly through membrane disarrangement [23]. Thus, both increase [24][25][26] and reduction [23] in β-cell CH content have been shown to reduce insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decrease in insulin secretion was observed under long-term inhibition of CH synthesis in insulin-secreting cells [23]. The associated impairment of GSIS is probably due to an effect of reduction in the protein isoprenylation and more importantly through membrane disarrangement [23]. Thus, both increase [24][25][26] and reduction [23] in β-cell CH content have been shown to reduce insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…The associated impairment of GSIS is probably due to an effect of reduction in the protein isoprenylation and more importantly through membrane disarrangement [23]. Thus, both increase [24][25][26] and reduction [23] in β-cell CH content have been shown to reduce insulin secretion. In conclusion, a critical concentration of cellular/membrane CH content is required for adequate secretion of insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of cellular biosynthesis by ‘statin’ drugs, or depletion of plasma membrane cholesterol by methyl-β-cyclodextrin (MCD), reduce glucose-stimulated insulin secretion (GSIS) and content in β-cells and islets; statin treatment also causes delayed ATP production, inflammation and β-cell apoptosis (Tscuhiya et al, 2010; Zuniga-Hertz et al, 2015). Paradoxically, accumulation of β-cell/islet cholesterol caused by low density lipoprotein (LDL) receptor deficiency (Souza et al, 2013) or loss of ATP binding cassette transporters (ABCA1, ABCG1) which efflux cholesterol to apolipoprotein A-I (apo A-I) and high density lipoprotein (HDL) (Kruit et al, 2012), is also associated with loss of GSIS, impaired calcium handling, increased reactive oxygen species (ROS), inflammation and apoptosis.…”
mentioning
confidence: 99%
“…2), a signaling step downstream to Fpp biosynthesis, inhibited cholesterol biosynthesis as well as GSIS. Based on these findings the authors concluded that protein prenylation and cholesterol biosynthetic pathways represent dual signaling mechanisms involved in GSIS [22]. Together, these findings provided additional clues with regard to regulatory roles of MVA-derived intermediates in GSIS.…”
Section: Studies Of Pharmacological Inhibitorsmentioning
confidence: 84%
“…Recent investigations by Zuniga-Hertz and associates have suggested additional roles for events in cellular cholesterol metabolic pathway in GSIS from INS-1E cells and mouse islets [22]. They observed a significant reduction in GSIS by simvastatin under acute conditions (2 h exposure).…”
Section: Studies Of Pharmacological Inhibitorsmentioning
confidence: 95%